The role of government effectiveness in suppressing corruption: Insights from the BRICS emerging economies - Khasawneh, Raed; Qudah, Anas Al; Hailat, Mahmoud (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines how government effectiveness contributes to suppressing corruption in BRICS countries—Brazil, Russia, India, China, and South Africa. Institutional theory and the theory of good governance frame the investigation into the interaction between government effectiveness, the rule of law, political stability, and economic growth in reducing corruption, addressing a significant research gap in emerging economies. Using panel data from the World Bank spanning from 2000 to 2021, the study employs dynamic panel analysis with the Panel Autoregressive Distributed Lag (ARDL) model and the Pooled Mean Group (PMG) estimator. While government effectiveness and the rule of law significantly reduce corruption in both the short and long term, political stability exhibits a dual effect: initially aggravating corruption in the short term but reinforcing anti-corruption reforms in the long run. The error correction term is negative and statistically significant, confirming a long-run relationship among our variables, with deviations corrected over approximately three years. The findings emphasize the need for policymakers in emerging economies to enhance institutional quality, strengthen the rule of law, and promote political stability to sustain anti-corruption efforts. While the study focuses on BRICS nations, the insights may be applicable to other emerging economies facing institutional weaknesses. Future research could explore the role of digital governance and cross-country political dynamics in shaping anti-corruption strategies.